The Relation of LBW, Mother’s Height with The Accidence of Stunting in the Children 6-24 months in Aceh Barat Regency - Itza Mulyani; Marniati Marniati; Hanif Muchdatul Ayunda (Journal of Nutrition Science, 2020)
Stunting is the condition of malnutrition where the height is not as proportional as the age which can be investigated by the measurement of height indicator based on age. Stunting signifies the lack of nutrition condition which has happened for a long time and requires the time for children to grow and to be fully recovered. According to Riskesdas 2013 report, the prevalence of stunting in children under five years is 37,2%. One of the provinces which regarded as a serious category is the Province of Aceh with a prevalence of 41,5% consists of the very short 20,1% and the short around 21.4%. The regency of Aceh Barat is one of the regencies in Aceh province. This regency still confronts severe nutritional issues, one of them is stunting with the prevalence of 40,9%. There are many factors related to the case of stunting, for example LBW (Low body weight), mother’s height.Objective: Knowing relation LBW, mother’s height with the accidence of stunting in the children 6-24 months old in Aceh Barat regency.Method: This study is an analytic observational study with the quantitative method. The design of this study is cross sectional which learn the correlation between independent variables and the dependent variables, where the measurement of both variables was conducted at the same time.Result: From 212 children, there are 55,66% children suffer from stunting. The result of bivariate analysis suggests that the factors related to stunting is low birth-weight (p <0.05). Height of the mother are not related to stunting cases (p> 0.05).Conclusion: the factors related to stunting is low birth-weight.